Tecnologia educativa digital para promoção da saúde mental de adolescentes: estudo de validação por especialistas - Farias, Quitéria Larissa Teodoro (2021)
Based on the impact of technologies on the daily lives of adolescents, and the strength they have been gaining as a result of social isolation in the face of the COVID-19 pandemic in the country and considering the fragility of the health service in reaching this public, especially in this period, the present study aims to validate a digital educational technology on the promotion of adolescents' mental health. It is outlined in a validation, descriptive study with a quantitative approach, in which the content and appearance validation by specialists of a course made available in VLE to promote the mental health of adolescents was developed. The validation was based on the Galvis-Panqueva referential, which divides the validation process in the Evaluation (selection of the judges and the judgment of the course by them) and the Administration (analysis of the highlighted notes and making the necessary changes). A total of 11 judges participated in the evaluation process, they were divided into two groups, namely: eight content judges, four of whom were experts in the areas of adolescent health and four in the area of mental health; and three technical judges in the information technology area. The content judges evaluated the course in terms of its objectives, structure/presentation and relevance. All criteria were considered valid, with CVI and p value >0.80 in all items, and an overall CVI of 0.98. Technical judges assessed the course for usability, functionality and efficiency. Most items were validated, except for four that obtained CVI 0.67 and p value of 0.49. The others had a CVI and a p-value >0.80, with an overall CVI of 0.85. The changes for the adequacy of these items in question were made based on the recommendations/ considerations made by the judges. All AVA material was reviewed and all suggestions made by the judges were incorporated, assisting in the process of updating, maintaining and verifying the AVA material and other actions necessary for the smooth running of the course. Therefore, the online course is valid to be used as a health education tool with adolescents, using material that addresses the specificities of these subjects, contributing to innovation in the health promotion process.